Verrucous carcinoma of the glottis and subglottis: a rare case report - Tiwari, Markandeya; Gonzaga Fernandes, Vinson Louis; Gouveia Pinto, Nina Margarida De; Sukhthankar, Isha Rajendra (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Verrucous carcinoma is a rare well differentiated squamous cell carcinoma with minimal metastatic potential. Its occurrence in the glottic and subglottic subsets of the larynx is another very rare entity. We highlight a case of an elderly male who was histopathologically diagnosed as verrucous carcinoma of the glottic and subglottic larynx. We shall discuss the clinical presentation, diagnosis, management, prognosis and postoperative follow up of the patient.